STUDIES ON CESTODE LARVAE, SCOLEX PLEURONECTIS MUELLER, 1788 FROM THE MARINE FISH PARACHAETURICHTHYS POLYNEMA BLEEKER, 1853 - VIJAYALAKSHMI, C.; VIJAYALAKSHMI, J.; RAO, M. DAMODARA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1995)
Parachaeturichthyspolynema is a marine goby fish. During the survey of cestode larval forms in marine fish, six types of cestode larval forms could be collected from this host alone. They belong to Scolex pleuronectis type, Scolex trilocularis and Scolex bilocularis.